Acute effects of motor imagery interventions and physical exercise on tongue strength and pain in healthy adults: a randomized, crossover trial - Tayfun Isik; Buse O. Kahraman; Turhan Kahraman (Bulletin of Faculty of Physical Therapy)
Abstract Background Motor imagery (MI) has increasingly been used in physiotherapy. Oral rehabilitation may be a potential application area for MI. The aim of this study is to investigate the acute effects of orofacial and tongue muscle strengthening exercises in the form of physical exercise and motor imagery on pain and tongue strength in healthy adults. Thirty asymptomatic adults were included in this trial. MI skills were evaluated using the Movement Imagery Questionnaire-Revised and the mental chronometer. The pain and strength were assessed using an algometer and a tongue pressure device. Following the baseline evaluations, three interventions: physical exercise, kinesthetic motor imagery, and visual motor imagery, were applied randomly on different days. Pain and tongue strength were re-evaluated immediately after the interventions. Results The physical exercise program did not significantly improve pain and tongue strength (p > 0.05). Following the kinesthetic MI training, a significant increase was detected (p = 0.016, d = 0.51) in the left masseter muscle pain threshold. Visual MI training resulted in improvements in anterior tongue strength (p = 0.002, d = 0.66) and left masseter muscle pain (p = 0.024, d = 0.40). Conclusions The present study suggests that different motor imagery strategies may have different effects on tongue muscle strength and pain threshold in healthy adults.